Speckle tracking carotid artery circumferential strain is a marker of arterial sclerosis but not coronary atherosis. Issue 9 (13th August 2018) - Patton, Daniel M.; Li, Terry; Hétu, Marie‐France; Day, Andrew G.; Preece, Erika; Matangi, Murray F.; Johri, Amer M.
Abstract: Purpose: Circumferential speckle tracking carotid artery strain is a novel method of quantifying vessel wall stiffness. We hypothesized that carotid wall stiffness would be associated with carotid intimal medial thickening (a medial process associated with risk factors), but not coronary artery disease (an intimal process). Methods: Bilateral carotid artery ultrasound was conducted on outpatients who had previously undergone elective coronary angiography. Mean carotid artery far wall circumferential strain (FWCS) was assessed for correlations with coronary angiographic stenosis, cardiac risk factors, carotid intima‐media thickness (CIMT), and carotid plaque. Results: One hundred and sixty five (165) patients were studied. No significant association was found between the presence of coronary artery disease on angiography and mean FWCS. FWCS was higher in current tobacco smokers. In addition, carotid strain was found to decrease with increased age ( r = −0.33, P < 0.001). When adjusted for pulse pressure (PP), FWCS/PP was negatively correlated with mean CIMT ( r = −0.29, P = 0.002) and bulb maximum plaque height ( r = −0.27, P = 0.004). Hypertension and diabetes were associated with decreased FWCS/PP (increased wall stiffness). Conclusions: While no clear relationship between carotid strain and coronary artery disease was observed, increased CIMT, carotid plaque, and cardiac risk factors were associated with decreased carotid strain. Further work is required to explore the relationship between carotid strain and cardiovascular events.